Some biological aspects of the hairy maggot blowfly, Chrysomya rufifacies (Macquart, 1842) (Diptera: Calliphoridae) - Begum, Shefali; Nasim, Md; Majumder, MZR (Bangladesh Journal of Zoology, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Bangladesh J. Zool. 35(2): 367-380, 2007